Synthesis, Structure and Biological Activity of 2-Methyl-5-nitro-6-phenylnicotinohydrazide-Based Hydrazones - Oralgazy A. Nurkenov; Anel Z. Mendibayeva; Serik D. Fazylov; Tulegen M. Seilkhanov; Saule K. Kabieva; Ardak K. Syzdykov; Ilya I. Kulakov; Aleksandr V. Iashnikov; Alexey S. Vasilchenko; Larisa E. Alkhimova; Ivan V. Kulakov (Molecules)
The synthetic availability and wide range of biological activity of hydrazides and hydrazones make them attractive subjects for investigation. In this study, we focused on synthesis of 2-methyl-5-nitro-6-phenylnicotinohydrazide-based hydrazones derived from the corresponding substituted aldehydes. The structure of the obtained compounds was studied using NMR spectroscopy and DFT calculations. After repeated recrystallization, all the synthesized compounds remained as mixtures of isomers. As a result of a detailed analysis, we found that the duplication and bifurcation of signals in the 1H NMR spectra for some atoms is a consequence of the existence of four isomers, namely Z-I, Z-II, E-I and E-II. Duplicate proton signals with a chemical shift difference of 0.1–0.2 ppm and in a ratio of about 2:1 were noticed in the experimental data. By modeling the structures of individual configurations and conformations, Gibbs free energy values were obtained, which allowed us to estimate the approximate content of rotamers for the E-isomer equal to 3:2, which coincided with experimental data. We also tested the antibacterial and antifungal activity of the synthesized compounds.